Control of exuT Activity for Galacturonate Transport by the Negative Regulator ExuR in Erwinia chrysanthemi EC16 - Venugopal Valmeekam; Yen-Lin Loh; Michael J. D. San Francisco (Molecular Plant-Microbe Interactions, 2001)
The negative regulatory protein ExuR in Erwinia chrysanthemi regulates expression of the galacturonate uptake (exuT) and utilization (uxaA, uxaB, uxaC) genes. We cloned and determined the nucleotide sequence of the exuR gene from E. chrysanthemi EC16. Analysis of the deduced amino acid sequence indicates that this protein possesses a helix-turn-helix motif and belongs to the GntR family of transcriptional repressors. Northern blot analysis and studies with transcriptional fusions of exuT in wild-type and exuR mutant backgrounds indicate that exuT transcription is deregulated in the exuR strain in vivo and in planta. [14C]-galacturonic acid uptake was constitutively high under inducing and noninducing conditions in the exuR mutant. Maximal exuT transcription activity was observed within 8 h of bacterial inoculation into potato tubers, well before any visible symptoms of disease were detected. This suggests that ExuT transport activity in E. chrysanthemi is important in the early stages of disease development.